THE AGE OF CHOKUSU BEDS IN THE KYZYL-DZHAR-CHOKUSU SECTION (THE SILURIAN OF NORTHWESTERN MONGOLIA) - Bondarenko O.B.; Minzhin C. (My University, 2000)
The rock succession and age of the Chokusu Beds in the Mt. Kyzyl-Dzhar-Chokusu section is considered to be either the Ludlovian-Pridolian or Wenlockian-early Ludlovian. The discrepancy resulted from a complicated geological structure and contradictory interpretations of rock ages on the basis of different groups of invertebrates (tabulates, heliolitids, rugoses, bryozoans, brachiopods). We reckon the beds to be of the Wenlockian age. It is not inconceivable that the upper Llandoverian and lower Ludlovian deposits are also present in the section.
Keywords: Silurian; Paleozoic::Silurian; Палеозой::Силурийская